2016
DOI: 10.1177/0363546515624471
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study of Objective and Subjective Clinical Results Between Double-Bundle and Single-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: In this prospective randomized controlled study, there was no significant difference in the incidence of secondary ACL injury and no difference in objective or subjective outcomes between the DB-HT and RTSB-PT reconstruction at 24-month follow-up. Age, sex, presence of meniscus injury, and BMI affected subjective KOOS subscale scores, while surgical technique did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 52 publications
6
63
0
2
Order By: Relevance
“…Additionally, height and IED on the coronal radiograph also predicted GD comprehensively with slightly improved accuracy ( R 2 : from 0.207 to 0.224). According to the multiple regression model and our criteria for additional harvesting GT, 40 (1) height <150 cm, (2) female sex, and (3) patients aged ≥30 years were at risk of having a GL <230 cm, whereas patients who (1) have an IED <70 mm and (2) are <150 cm in height were also at risk of having a GD <5.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, height and IED on the coronal radiograph also predicted GD comprehensively with slightly improved accuracy ( R 2 : from 0.207 to 0.224). According to the multiple regression model and our criteria for additional harvesting GT, 40 (1) height <150 cm, (2) female sex, and (3) patients aged ≥30 years were at risk of having a GL <230 cm, whereas patients who (1) have an IED <70 mm and (2) are <150 cm in height were also at risk of having a GD <5.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…1 In their prospective randomized controlled study (RCT), Sasaki et al reported there was no significant difference in objective or subjective outcomes between anatomical DB ACLR with an HT graft and anatomical rectangular tunnel single-bundle ACLR with a BPTB graft at 24-month follow-up. 25 Although this RCT could be considered a very high-level study, the author's use of different tibial fixation methods may have influenced the results of their study. In addition, their study lacked quantitative evaluation of femoral and tibial tunnel locations.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few previous studies that have compared BPTB and HT grafts in anatomical ACLR using either the lateral intercondylar ridge as an index or with validation of tunnel positions. 25 In our institution, we have performed anatomical ACLR with BPTB and HT grafts using the same methods since 2012 including anatomical concept, fixation device, initial graft tension, or postoperative rehabilitation protocol.…”
mentioning
confidence: 99%
“…2,3 In the midterm, several studies presented clinical outcomes without being able to detect significant differences between the DB and SB technique in subjective and objective outcome measures. 4,5 Some studies claimed more rotational stability for DB ACL-R, 5-7 but systematic reviews failed to prove significant differences when comparing SB and DB ACL-R outcomes. 6,8 Often, only functional aspects were described in high-quality studies; in particular, knee stability or laxity after ACL-R was regarded as the primary endpoint.…”
Section: See Related Article On Page 996mentioning
confidence: 99%